Credit situation of microenterprises in Poland – trends and implications - Andrzejak, Maria; Weremczuk, Arkadiusz; Wielechowski, Michał (Turystyka i Rozwój Regionalny, 2022)
The study aim is to characterise and assess the credit situation of microenterprises in Poland in 2020-2022. We focus on credit dynamics and quality, including total loans, investment loans, working capital loans, and overdrafts. We use monthly data from Polish Credit Information Bureau (BIK). The research covers the period between July 2020 and July 2022. We observe a significant increase in the dynamics of loans granted to microenterprises at the beginning of 2021 and a downward trend in the following analysed months. The fluctuation is similar for investment loans, working capital loans, and overdrafts. We claim that a decrease in the dynamics and interest in loans by microenterprises is not dependent only on the COVID-19 pandemic. A substantial reduction in the value of the Portfolio Quality Index is noticed during the first months of the analysed period (second half of 2020). Then its value stabilizes at a low level. The Index of Portfolio Quality for all analysed industries shows similar values. The analysis results indicate an unfavourable trend that should worry the microentrepreneurs sector and may also negatively affect the entire economy.